2001
DOI: 10.1111/j.1834-7819.2001.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of oral hairy leukoplakia in South Australia

Abstract: Background: The features of oral hairy leukoplakia (OHL) have been widely reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Chattopadhyay et al (10) verified a prevalence of 18.0% in North Carolina. Logan et al (23) in Australia, Eyeson et al (24) in South London, Bemdick et al (25) in Cambodia, Ramirez‐Amador et al (26) in Mexico and Bravo et al (27) in Venezuela verified an OHL prevalence of 45.2%, 9.95%, 45.5%, 22.6% and 53.0% respectively. These differences may be related to methodological issues.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Chattopadhyay et al (10) verified a prevalence of 18.0% in North Carolina. Logan et al (23) in Australia, Eyeson et al (24) in South London, Bemdick et al (25) in Cambodia, Ramirez‐Amador et al (26) in Mexico and Bravo et al (27) in Venezuela verified an OHL prevalence of 45.2%, 9.95%, 45.5%, 22.6% and 53.0% respectively. These differences may be related to methodological issues.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of authors have used the division of 200 cells/mm 3 for the CD4 T lymphocyte count, as did this study (2, 10, 11, 14, 15, 23, 27, 29, 30). The results of the present study regarding the CD4 T lymphocyte count are in accordance with the studies of Logan et al (23), Barr et al (31), Kolokotronis et al (32) and Greenspan et al (33), which found no relation between the OHL and the CD4 lymphocyte count. However, we observed that, proportionally, the OHL was slightly higher in patients who showed a CD4 T lymphocyte count of <200 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a regressive, but not statistically significant, effect of ART on OHL. Various studies have documented a reduced prevalence of OHL in patients who are taking ART [16, 31, 35]. This can be attributed to antiviral effect of ART.…”
Section: Discussionmentioning
confidence: 99%
“…Frydrych, Davies, et al 29 Use of pilocarpine as a sialogogue in patients with radiation induced xerostomia. Katelaris, Widmer, et al 30 Screening for latex allergy with a questionnaire: comparison with latex skin testing -Logan, Coates, Pierce, Wilson 31 A retrospective analysis of oral hairy leukoplakia in South Australia. Kinane, Marshall 32 Periodontal manifestations of systemic disease.…”
Section: Australian Dental Journalmentioning
confidence: 99%